Some Nonunique Common Fixed Point Theorems in Symmetric Spaces through Property - E. Karapınar; D. K. Patel; M. Imdad; D. Gopal (International Journal of Mathematics and Mathematical Sciences)
We introduce a new class of mappings satisfying the “common limit range property” in symmetric spaces and utilize the same to establish common fixed point theorems for such mappings in symmetric spaces. Our results generalize and improve some recent results contained in the literature of metric fixed point theory. Some illustrative examples to highlight the realized improvements are also furnished.